Kritis Terhadap Dampak Media Sosial, Demi Mencegah Turunnya Kualitas Generasi Muda - Muhamad Hobiri; Noor Adiyati; Nadila Oktaviany; M. Syah Bintang M.P; Dody Wahyudi; Alvianur Alvianur; M. Febri Aditya; M. Luthfi Setiarno Putra (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Social media now plays an important role in everyday life and has a great impact on society and people. The drawbacks of social media are discussed in this study. Problems that arise from social media include the rise of fake news, digital addiction, mental health problems, and cyberbullying. To optimize the positive impact of social media and reduce its negative impact, social media must be used wisely. This study aims to analyze the effect of social media use on adolescent mental health. This study used a survey method involving 200 adolescents aged 13-18 years as respondents. Data was collected through a questionnaire that measured the frequency of social media use, types of content consumed, and mental health indicators such as depression and anxiety. The results showed that there was a positive correlation between the frequency of social media use and the level of depression and anxiety in adolescents. In addition, exposure to negative content such as cyberbullying and others also contributed to the decline in mental health. This study concludes that excessive and unhealthy social media use can negatively impact adolescents' mental health.